Women and Investment Decision in Sharia Instruments: Moderating Effect of Financial Spirituality Orientation - Amaroh, Siti; Prasetyoningrum, Ari Kristin; Husain, Husna (SCAD Independent, 2024)
This research is based on a gap in authority between men and women in making investment decisions where women are considered less financially literate and less struggling. Therefore, this study examines how financial literacy and trust affect women’s investment decisions in Sharia instruments with financial spirituality orientation as a moderating factor. The sample was selected from 256 women on the northeastern coast of Central Java, Indonesia. Structural Equation Modeling with a Partial Least Square method was used to test the data. The findings showed that the higher the financial literacy, trust, and financial spirituality orientation, the better the decision level in the Sharia investment decisions. The financial spirituality orientation strengthens the influence of financial literacy on Sharia investment decisions. However, financial spiritual orientation cannot intervene in trust in financial institutions. This finding suggests that women consider their spiritual beliefs while making financial decisions, but spirituality cannot nullify trust’s ability to affect Sharia investment choices. The implication is that when gender equality is acknowledged, women can get an education, work, income, and be more financially literate. The role of financial spirituality is in its mission of establishing the life-balances.